Research of organisation specifics of shooting process in the creation of an audiovisual product - Yu. V. Vorontsova; A. Yu. Mazur (Вестник университета, 2021)
This article presents a study of the organisation of the shooting process, taking into account the authentic features of five films by the Spanish filmmaker and photographer Carlos Saura, where the principle of “photography” was the basis for the construction of the frame. Saura made a series of films based on the flamenco culture, reflecting his experiments to establish the relationship between the beat of the music and dance and the rhythm of the set-up and movement of the camera. Carlos Saura’s work is characterised by a relationship between past and future, reality and fiction. When making a film, it is necessary to think photographically and critically, especially on the issue of national identity. The photographic act itself is an immediate transformation of the present referent into a petrified past. Elements of photography often add a strong dose of time to the movement you want to follow, but this possible action will always remain in the frame. Saura expands in a certain way what restricts the photographic act in such a way that the captured image overflows spacetime. For Saura, the relationship between photography and film becomes one of the most important components of the script in the films examined.